Sacred Places in the Construction of Indigenous Environmentalism - Harvey, Graham (Journal for the study of religion, nature and culture, 2002)
Indigenous people have often been linked with ‘nature’. Recently this has been complimentary, based on the assessment that nature is good, but this was not always the case. This paper is interested in the construction of indigeneity as environmentalist, and in the construction of environmentalism with reference to indigeneity. It is particularly concerned with challenging various relevant Western notions from the perspective that indigenous religious traditions might offer quite different ontologies and engagements. It takes note of the wider context of a conflict between colonialism and sovereignty which entangle these issues in traumatic crises but also underpin significant possibilities for change.